Skills for industrialisation in sub-Saharan African countries: why is systemic reform of technical and vocational systems so persistently unsuccessful?. (3rd July 2022) - Allais, Stephanie
ABSTRACT: This paper examines three interrelated factors outside of formal provision of technical and vocational education and training (TVET) in sub-Saharan Africa that have undermined TVET systems. The first is the process, pace, and levels of industrialisation, which has had a direct effect on TVET provision: low numbers of well-paying jobs requiring technical expertise. This has an indirect effect, which is the second crucial factor: lack of economic development and change in labour markets. There are very few jobs that would be considered 'middle class' or 'mid-level' in wealthy countries. Most people are in survivalist work. An international consensus since the 2000s on palliative approaches to development which address the effects but not the causes of the lack of economic development in Africa has resulted in mass poor quality provision of education—the third factor. Education systems are rapidly expanding and achievement levels rising, in the context of very little possibility of labour market rewards for most people, and substantial labour market rewards confined mainly to graduates. This reinforces deeply embedded cultural preferences for general education, which originate in the type of education systems established by colonial powers, as well as the relationships between educational credentials and elite jobs.